2012
DOI: 10.1021/es203896t
|View full text |Cite
|
Sign up to set email alerts
|

Steroid Hormone Runoff from Agricultural Test Plots Applied with Municipal Biosolids

Abstract: ABSTRACT:The potential presence of steroid hormones in runoff from sites where biosolids have been used as agricultural fertilizers is an environmental concern. A study was conducted to assess the potential for runoff of seventeen different hormones and two sterols, including androgens, estrogens, and progestogens from agricultural test plots. The field containing the test plots had been applied with biosolids for the first time immediately prior to this study. Target compounds were isolated by solid-phase ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 53 publications
2
47
1
1
Order By: Relevance
“…Barel-Cohen et al [49] reported that 10 ng L −1 as the Lowest Observable Effect Level (LOEL) for total estrogen (17␤-estradiol + estrone). The results of this study are similar to previous reports by Mansell et al [20] and Yang et al [50]. DeLaune and Moore [51] also showed that manure type, application rate, and time until the first runoff event after manure application can affect the transport of steroid hormones to surface water.…”
Section: Bulk Steroid Hormone Transportsupporting
confidence: 92%
“…Barel-Cohen et al [49] reported that 10 ng L −1 as the Lowest Observable Effect Level (LOEL) for total estrogen (17␤-estradiol + estrone). The results of this study are similar to previous reports by Mansell et al [20] and Yang et al [50]. DeLaune and Moore [51] also showed that manure type, application rate, and time until the first runoff event after manure application can affect the transport of steroid hormones to surface water.…”
Section: Bulk Steroid Hormone Transportsupporting
confidence: 92%
“…Soil surface managements also reduced the impact of the kinetic energy of rain drops, and increased rainfall interception and storage. These beneficial effects are closely related to mulch application rates and diversity of materials (Adekalu et al, 2007;Jordán et al, 2010;Yang et al, 2012). Montenegro et al (2013) conducted a simulated rainfall experiment by using 3 surface covers with different mulching applications, and observed 51% reduction in runoff peak value under a mulch cover of 4 t ha −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Further, the aqueous solubility for EE2 (table 1) is less than that of other steroid hormones, which would support less EE2 dissolved in surface runoff. However, Yang et al (2012) found that 95% of progesterone was identified in the dissolved phase rather than the particle-associated phase. Hildebrand et al (2006) found that EE2 did not exhibit a specific trend of desorption across different initial EE2 concentrations.…”
Section: Effect Of Incorporation On Ee2 In Runoffmentioning
confidence: 97%
“…They analyzed for nine different natural and synthetic hormones (four natural estrogens, three synthetic androgens, and two natural androgens), and none were detected in more than 19% of the samples from drainage ditches and 23% of the samples from tile drains, except estrone, which was detected in 20% and 52% of samples from drainage ditches and tile drains, respectively. Research reported by Yang et al (2012) found different detection frequencies of hormones depending on the timing of rainfall. Previous work by the authors noted less than 21% detections of steroid hormones or their metabolites in surface runoff samples collected during rainfall simulations on row crop production areas receiving stockpiled or composted beef feedlot manure (data not shown).…”
mentioning
confidence: 93%